Question
upstudy study bank question image url

Find the solution to the system by the substitution method. Check your answer. \[ \begin{array}{ll}-x+3 y=-17 & \text { (1) } \\ 4 x-y=24 & \text { (2) }\end{array} \]

Ask by Fuentes Lyons. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solution is \( x = 5 \) and \( y = -4 \).

Solution

Certainly! Let's solve the given system of equations using the **substitution method** and then verify the solution. \[ \begin{cases} -\,x + 3y = -17 \quad \text{(1)} \\ 4x - y = 24 \quad \text{(2)} \end{cases} \] ### Step 1: Solve one equation for one variable Let's solve **Equation (1)** for \( x \): \[ -\,x + 3y = -17 \] Add \( x \) to both sides: \[ 3y = x - 17 \] Now, solve for \( x \): \[ x = 3y + 17 \quad \text{(3)} \] ### Step 2: Substitute into the other equation Now, substitute \( x = 3y + 17 \) from **Equation (3)** into **Equation (2)**: \[ 4x - y = 24 \] Substituting: \[ 4(3y + 17) - y = 24 \] Expand the multiplication: \[ 12y + 68 - y = 24 \] Combine like terms: \[ 11y + 68 = 24 \] Subtract 68 from both sides: \[ 11y = 24 - 68 \] \[ 11y = -44 \] Divide both sides by 11: \[ y = -4 \] ### Step 3: Find the other variable Now that we have \( y = -4 \), substitute this back into **Equation (3)** to find \( x \): \[ x = 3y + 17 \] \[ x = 3(-4) + 17 \] \[ x = -12 + 17 \] \[ x = 5 \] ### Solution \[ x = 5, \quad y = -4 \] ### Step 4: Check the solution Let's verify the solution by substituting \( x = 5 \) and \( y = -4 \) back into both original equations. **Check in Equation (1):** \[ -\,x + 3y = -17 \] \[ -5 + 3(-4) = -17 \] \[ -5 - 12 = -17 \] \[ -17 = -17 \quad \text{✓} \] **Check in Equation (2):** \[ 4x - y = 24 \] \[ 4(5) - (-4) = 24 \] \[ 20 + 4 = 24 \] \[ 24 = 24 \quad \text{✓} \] Both equations are satisfied, so the solution is correct. ### Final Answer \[ \boxed{\,x = 5,\quad y = -4\,} \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To solve the system of equations using the substitution method, we start with the equations: 1) \(-x + 3y = -17\) 2) \(4x - y = 24\) Let's isolate \(x\) in equation (1): \(-x = -17 - 3y\) Multiplying everything by -1 gives: \(x = 17 + 3y\) (Equation 3) Next, we substitute Equation 3 into Equation 2: Substituting \(x\) in \(4x - y = 24\): \[ 4(17 + 3y) - y = 24 \] Now, distribute: \[ 68 + 12y - y = 24 \] Combine like terms: \[ 68 + 11y = 24 \] Now, isolate \(y\): \[ 11y = 24 - 68 \] \[ 11y = -44 \] Dividing by 11: \[ y = -4 \] Now that we have \(y\), we'll substitute it back into Equation 3 to find \(x\): \[ x = 17 + 3(-4) \] \[ x = 17 - 12 \] \[ x = 5 \] So, the solution to the system is \(x = 5\) and \(y = -4\). To check our answer, we substitute \(x = 5\) and \(y = -4\) back into the original equations: For equation (1): \[-(5) + 3(-4) = -5 - 12 = -17\] (True) For equation (2): \[4(5) - (-4) = 20 + 4 = 24\] (True) Both equations are satisfied, so our solution is confirmed: **\(x = 5, y = -4\)**.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy